Dynamics of Welded Rails Gap and Hardness of Rail Base - T.I. Zaitseva; I.V. Blinova; A.M. Uzdin (International Journal of Applied Mechanics and Engineering, 2020)
The problem of gap estimation for a break of a continuous welded rail is studied. The track is represented as a semi-infinite rod on elastic-based damping. Static and dynamic solutions are obtained. It is shown that during the rail break, the dynamic factor does not exceed 1.5. We derive equations for thermal deformation of the welded rail of jointless track on an elastic foundation in the presence of the insert into the base with another characteristic stiffness. It is shown that the presence of the insertion of up to 20 % of the length of the rail, with both large and small stiffness, has a little effect on the stress-strain state (SSS) of the track. The presence of a rigid insert may increase the clearance of an accidental break of the rail, which has a negative effect on traffic safety.